Sucrose Content Loss in the Harvest-Loading-Transport System at PG Sindang Laut and PG Tersana Baru, Cirebon - Bantacut, Tajuddin; sukardi, Sukardi; Supatma, Irfan Ardiansyah (Jurnal Teknologi Pertanian, 2012)
The loss of sucrose in the cane sugar production could reach 35%. Harvesting, loading and transporting the sugarcane contribute significantly to the total lost prior to milling, ranging from 5â25%. The aims of this research were to identify factors that influence the harvest-loading-transport system, to analyze the pattern of sucrose content loss in sugar cane before milling, and to recommend means of improving the harvest-loading-transport system according to the exixting condition of sugar factories. The implementation of the harvest-loading-transport system can be influenced by many factors, among them are the factors determining the chopping schedule (T-score) which consist of planting time, difference between below purity level and upper purity level, average sucrose content, difference between upper sucrose content and below sucrose content, maturity factor, increase coefficient, durability coefficient, shoot auger pest, plant condition, and distance. The felling system is determined by the plantation layout, infrastructure (road, bridge conditions), topography, climate and weather, and equipment for fire tackling.Keywords: cane sugar production, sucrose content, sucrose losses, harvest-loading-transport